Employment in Health and Long-Term Care Sector in European Countries - Erika Schulz (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Health care is an important sector in all European countries showing a high dynamic in the past. In 2011 about 23 million persons were employed in health and social care, that is to say 10.4 % of total employment. The share of health care expenditures in GDP was 10 %. The health care workforce increased despite the overall trend of declining employment also during the economic crisis. The high dynamic in health care can be explained by demographic changes as well as by other non-demographic drivers. Due to the ageing of the population a further increase in the demand for health workforce is expected. This paper gives an overview of the health and social workforce in the EU Member States based on the EU labour force survey. It focuses on the current situation and the changes in the last years as well as the differences across the Member States in the three main areas human health care, residential care, and social work.
Additional information: This publication was produced as part of the NEUJOBS project, funded by the European Commission through the 7th Framework Programme under contract no. 266833 (http://www.neujobs).; info:eu-repo/grantAgreement/EC/FP7/266833
Keywords: 330; Beschäftigungseffekt; Pflegeversicherung; Pflegebedürftigkeit; Gesundheitsberufe; EU-Staaten